Monitoring of the Response of the Sagamore Parkway Bridge and its Foundations During a Live Load Test. Issue 3 (March 2021) - Han, Fei; Marashi, Mehdi; Prezzi, Monica; Salgado, Rodrigo; Wells, Timothy; Zaheer, Mir
In this paper, we report the results of a live load test performed on the Sagamore Parkway bridge over the Wabash River, Indiana. The seven-span concrete bridge was constructed from 2016 to 2018 to replace the old, east-bound bridge. The main goals of the live load test were: (i) to study the transfer of the live loads from the bridge pier to the foundation elements and the distribution of live loads among the individual piles supporting the bridge pier; and (ii) to verify the assumptions (e.g., regarding the pile cap resistance) made in bridge foundation design. For these purposes, one of the interior piers (Pier 7) of the bridge and the fifteen pipe piles supporting it were instrumented with vibrating-wire strain gauges. With the bridge temporarily closed to traffic, the live load test was performed by parking twelve loaded triaxle trucks at specific locations on the bridge deck near Pier 7 in March 2019. The truck loads were applied in seven stages, simulating the driving of several trucks over the bridge pier. The settlement of the pier was measured using a digital level during the live load test. The data from the strain gauge readings were processed to produce the history of load distribution within the cross section of the pier and among the piles in the pile group during the seven stages of the live load test. The soil in contact with the pile cap carried about half of the total live load.